Contemporary police strategies of crime control in U.S. and China: a comparative study - Wang, Liang (Crime, law and social change, 2016)
This study takes a comparative approach to examining the contemporary police change in controlling crime in American and China. We attempt to achieve two primary objectives. First, we critically evaluate American and Chinese police innovations including the theoretical framework, police operations, and associated effectiveness. Second, we attempt to identify the utility of innovative strategies that can be shared by both sides. Five innovative strategies adopted by American police agencies in the past 25 years are summarized and reviewed. On the other side, the primary strategy utilized in crime control is Chinese style of community policing. After comparison of the policing strategies in the two countries, it is self evident that the implementation of community policing in China is broader and more in-depth than American police. Chinese police organizations can benefit from the implementation of problem-oriented policing accumulated from their American counterpart. Finally, we argue that hot spots policing and predictive policing do not have significant utility in the Chinese setting.